Design and Implementation of Visible Light Communication based Toys - Najihah, Ain; Hadi Habaebi, Mohamed; Abdul Rahman, Farah Abdul Rahman (Institute of Advanced Engineering and Science, 2019)
This paper aims to design a smart visible light communication based toy system equipped with laser sensors that can send and receive the data message based on the conversion of data from ASCII to binary code. The system intents to offer two-ways communication toys that will be a new medium for educational purposes for kids in their developmental stages in which both players can send and receive the data to and from each other and equipped with sound indicator module to alert the player. Lastly, functionality and system testing were conducted to verify the functionalities of the system.